Application and progress of palliative therapy in advanced gastric carcinomas - Luo, Xiao-fan; Luo, Ye-hao; Zhao, Xin-yi; Lin, Xue-ting; Li, Wen-ling; Jie, Jie; Wu, Di; Fang, Gang; Pang, Yu-zhou; Huang, An (Frontiers in Oncology, 2023)
Gastric carcinomas have high morbidity and mortality. It produces no noticeable symptoms in the early stage while causing complex complications in its advanced stage, making treatment difficult. Palliative therapy aims to relieve the symptoms of cancer patients and focuses on improving their quality of life. At present, five palliative therapies for advanced gastric carcinomas are offered: resection, gastrojejunostomy, stenting, chemotherapy, and radiotherapy. In recent years, palliative therapy has been used in the clinical treatment of advanced gastric carcinomas and related complications because of its efficacy in gastric outlet obstruction and gastric bleeding. In the future, multimodal and interdisciplinary palliative therapies can be applied to control general symptoms to improve patients’ condition, prolong their lifespan and improve their quality of life.